What laws determine progress? An Indian contribution to the idea of progress based on Mahadev Govind Ranade's works, 1870–1901. Issue 2 (4th March 2018) - Bach, Maria
ABSTRACT: By the late nineteenth century, the school of "Indian Political Economy" was founded to understand India's extreme poverty and deindustrialisation. This paper examines how Mahadev Govind Ranade (the school's founder) conceptualised progress by tracing its origins and evaluating how it was formulated to reconcile theory with India's political and socio-economic reality. Ranade identified specific Indian determinants of progress: the centrifugal nature of Indian politics; the dependence of a colonial economy; and its refutable role within the international division of labour theory.